Multi-parametric non-contrast cardiac magnetic resonance for the differentiation between cardiac amyloidosis and hypertrophic cardiomyopathy - Steen, Henning; Montenbruck, Moritz; Kallifatidis, Alexandros; André, Florian; Frey, Norbert; Kelle, Sebastian; Korosoglou, Grigorios (Clinical research in cardiology, 2023)
Aim To evaluate the ability of fast strain-encoded (SENC) cardiac magnetic resonance (CMR) derived myocardial strain and native T1 mapping to discriminate between hypertrophic cardiomyopathy (HCM) and cardiac amyloidosis.Methods Ninety nine patients (57 with hypertrophic cardiomyopathy and 42 with cardiac amyloidosis) were systematically analysed. LV-ejection fraction, LV-mass index, septal wall thickness and native T1 mapping values were assessed. In addition, global circumferential and longitudinal strain and segmental circumferential and longitudinal strain in basal, mid-ventricular, and apical segments were calculated. A ratio was built by dividing native T1 values by basal segmental strain (T1-to-basal segmental strain ratio).Results Myocardial strain was equally distributed in apical and basal segments in HCM patients, whereas an apical sparing with less impaired apical strain was noticed in cardiac amyloidosis (apical-to-basal-ratio of 1.01 +/- 0.23 versus 1.20 +/- 0.28, p < 0.001). T1 values were significantly higher in amyloidosis compared to HCM patients (1170.7 +/- 66.4 ms versus 1078.3 +/- 57.4ms, p < 0.001). The T1-to-basal segmental strain ratio exhibited high accuracy for the differentiation between the two clinical entities (Sensitivity = 85%, Specificity = 77%, AUC = 0.90, 95% CI = 0.81-0.95, p < 0.001). Multivariable analysis showed that age and the T1-to-basal-strain-ratio were the most robust factors for the differentiation between HCM and cardiac amyloidosis.Conclusion The T1-to-basal-segmental strain ratio, combining information from segmental circumferential and longitudinal strain and native T1 mapping aids the differentiation between HCM and cardiac amyloidosis with high accuracy and within a fast CMR protocol, obviating the need for contrast agent administration.